2014
DOI: 10.3168/jds.2013-7504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequency of feed delivery on the behavior and productivity of lactating dairy cows

Abstract: The objective of this study was to determine the effect of feed delivery frequency on the behavioral patterns and productivity of lactating dairy cows. Twelve freestall-housed, lactating Holstein dairy cows, including 6 primiparous (PP) and 6 multiparous (MP), milked 3×/d (at 1400, 2200, and 0600h), were exposed to each of 3 treatments (over 21-d periods) in a replicated Latin square design. Treatments included feed delivery frequency of (1) 1×/d (at 1400 h), (2) 2×/d (at 1400 and 2200 h), and (3) 3×/d (at 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
27
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 29 publications
16
27
2
3
Order By: Relevance
“…The moderate sensitivity for classification of feeding and nonfeeding behavior may have been due to the necessary assumption that cows maintained a single behavior for the 20-min window represented by the instantaneous scan sample. Standing, lying, and feeding bouts are generally much longer than this in duration, as reported here and previously; for example, Blackie et al (2011) reported lying and standing bouts averaged greater than 60 min, similar to Hart et al (2014), who also reported average feeding bouts exceeding than 24 min for primi-and multiparous cows. However, it is possible that changes in activity during these periods resulted in misclassification within the decision tree algorithm.…”
Section: Barker Et Alsupporting
confidence: 83%
“…The moderate sensitivity for classification of feeding and nonfeeding behavior may have been due to the necessary assumption that cows maintained a single behavior for the 20-min window represented by the instantaneous scan sample. Standing, lying, and feeding bouts are generally much longer than this in duration, as reported here and previously; for example, Blackie et al (2011) reported lying and standing bouts averaged greater than 60 min, similar to Hart et al (2014), who also reported average feeding bouts exceeding than 24 min for primi-and multiparous cows. However, it is possible that changes in activity during these periods resulted in misclassification within the decision tree algorithm.…”
Section: Barker Et Alsupporting
confidence: 83%
“…The results of our milk yield and composition variables were consistent with other published results (Chamberlin et al, 2013;Hart et al, 2014;Kessel et al, 2008;Kessler et al, 2014;Rastani et al, 2005;De Vries and Veerkamp, 2000). Even with no observed significant effects of addition of any type of supplements used in this study on milk yield, the inclusion of supplements seems to be increase milk production in PP cows.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a trend for milk yield to decrease (P = 0.097) with increasing feeding frequency (21.2 vs. 20.4 ± 1.59 kg/d for once-vs. twice-daily feeding, respectively). This observation was not expected because it is generally believed that increased feed frequency would result in increased feed intake and, as a consequence, increased milk yield (Hart et al, 2014); however, such responses are not always observed (Nocek and Braund, 1985). Increasing feeding frequency has been observed to increase the percentage of milk fat (Nocek and Braund, 1985), which has been attributed to the stabilization of the pH in the rumen.…”
Section: Dmi Milk Production and Compositionmentioning
confidence: 98%